PENERAPAN PENERAPAN MANAJEMEN PENDIDIKAN DI SEKOLAH MENENGAH ATAS MELALUI INOVASI: Manajemen pendidikan sekolah - ELSA YUSMINAR, ELSA (SABA JAYA PUBLISHER, 2024)
ABSTRACT In improving the quality of education, there must be continuous performance and quality improvement. Then not only talking about quality but strategy in education management in schools is very important because a strategy is needed so that the goals to be achieved are achieved so that they can run properly. Furthermore, the application through innovation is no less important because innovation has a drive to achieve goals. School education management is a form of successful educational management scope, such as: (1) students are satisfied with educational services; (2) education customers are satisfied with services to their students.